Diet and breast cancer - Szuster, Ewa; Kostrzewska, Paulina; Pawlikowska-Gorzelańczyk, Anna; Mandera-Grygierzec, Amanda (Journal of Education, Health and Sport, 2022)
Breast cancer is the most common malignancy among women. We conducted an analysis to investigate the impact of diet on breast cancer. Well-balanced diet is a mandatory part of a healthy lifestyle, and consequently, it is very important in prevention of breast cancer. High intake of fruits and vegetables, proper BMI and low intake of alcohol and fried food rich in saturated fatty acids are common known to be anti-cancer prevention. Soy food, black pepper and turmeric are suggested to inhibit cancer’s proliferation. Dietitians and oncologists should educate their patients about healthy lifestyle patterns.